LE2Pol: the Leicester dual-beam imaging polarimeter. Issue 1 (15th February 2023) - Wiersema, K; Starling, R L C; Campagnolo, J C N; Thanki, D; McErlean, R
Abstract: We describe the development, construction, data analysis, initial calibration, and first results of the Leicester dual-beam imaging polarimeter (LE2Pol), an inexpensive dual-beam optical imaging polarimeter. LE2Pol is designed for a 20-inch telescope at the observatory of the University of Leicester, but can also be used as a visiting instrument on a wide range of small telescopes (≲1 m). We show how simple imaging polarimeters on small telescopes can be used to provide useful scientific and educational data at low cost.